Applicability of SIRIM Green 5-S Model for productivity & business growth in Malaysia. Issue 2 (9th March 2015) - Sam Ho, Dr Jacques Martin and Professor Claudio Baccarani, Professor; Ho, Sam; Mohd Hashim, Abdul Ghani Bin; Mohd Idris, Mohd Azman
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Based on the TQM Model developed in a previous paper published at the TQMJ, the authors have a chance to test out the model in a number of firms in Malaysia through Standards and Industrial Research Institute of Malaysia (SIRIM). Furthermore, riding on the success, SIRIM has named it as the SIRIM Green 5-S Model. As a result, the purpose of this paper is to share the experience of the "SIRIM Green 5-S Model for business sustainability and organisational development". Design/methodology/approach – Based on questionnaire survey of 81 organisations cutting across different industries in Malaysia (+2 in-depth interview), this research is to study three research questions relating to 5-S and Lean Management. RQ1: is the 5-S Practices a necessary and sufficient condition for Organisational Productivity (OP)?; RQ2: is the L5S Practices a necessary and sufficient condition for Business Growth (BG)?; and RQ3: is the SIRIM Green 5-S applicable and effective for OP and BG? Findings – There is a ranking of effectiveness of the 5-S and L5S criteria in quality improvement. There is a strong correlation of the 5-S and L5S functions in quality improvement. How to use Green 5-S Model to improve productivity, increase sales and reduced cost. How to use Green 5-S Model to establish and maintain quality environment for OP and BG in order to provide competitiveness for business and industries of Malaysia. Originality/value – Since 1993, the authors used the proprietary 5-S Checklist for training and consultancy in no less than ten countries with over 50, 000 persons from around 2, 000 organisatioins world-wide. On the other hand, HKSAR takes the lead in the global oil energy consumption/GPD. The experience will be shared in this paper.